Physical fitness and skiing technique in elite biathletes with different efficiency of performance - Myakinchenko E.B.; Volkov M.V.; Missina S.S.; Kriuchkov A.S. (Theory and Practice of Physical Culture, 2025)
Abstract Objective of the study. To identify the values of a morphology, physical fitness and skiing technique in high-class biathletes with a different efficiency of performance (PE). Methods and structure of the study. The PE criterion was the average points in one race during the competitive period among 46 leading Russian biathletes, “purified” from the influence of the shooting accuracy and the differences in physical fitness. Results and conclusions. Athletes with high PE had shorter gliding phase, lower push-off activity with higher vertical oscillations of the BCM, but lower losses of horizontal speed in the cycle. Such athletes had higher body and muscle mass, as well as better aerobic power, especially of upper body.